Pengaruh Kecerdasan Intelektual Dan Keterampilan Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan Bank Bjb Kantor Cabang Cianjur) - Priyanti Handayani; Acep Samsudin; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of intellectual intelligence and work skills on the performance of employees of Bank BJB Cianjur Branch Office. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique in this study used a saturated sample of 127 employees of Bank BJB Cianjur Branch Office. The types of data used in this study are primary data and secondary data. The measurement of this study used a Likert scale. The results of this study indicate that (1) there is a positive and significant influence between intellectual intelligence on the performance of employees of Bank BJB Cianjur Branch Office of 0.431. (2) there is a positive and significant influence between work skills on the performance of Bank BJB employees at the Cianjur Branch Office of 0.702. (3) there is a positive and significant influence between intellectual intelligence and work skills on employee performance with a very strong interpretation. Based on the calculation results show multiple linear regression equations, as follows: Y = 4.150 + 0.158X1 + 0.567X2. The contribution given by the variable of intellectual intelligence and work skills is 73.3% and the remaining 26.7% is influenced by other factors not included in this study. Keywords: Intellectual Intelligence, Work Skills, Employee Performance